Nie 'n kans vat of 'n kans vermy Die, maar alle kanse benut! 'n Sosio-retoriese waardering van Prediker 11:1- 6 - Viviers, Hennie (Verbum et ecclesia, 1997)
No taking or avoiding of chances, but utilising all chances! A sociorhetorical appreciation of Ecclesiastes 11:1-6. The book of Vemon K Robbins, Exploring the texture of texts: A guide to sodo-rhetorical interpretation (Valley Forge: Trinity Press, 1996), is used to analyse the short, but complicated text, Ecclesiastes 11:1-6. Sodorhetorical criticism provides for a sophisticated grasp on the complex phenomenon, "text". The analysis of the different textures of a text (inner, inter-, sodal and cultural, ideological and sacred) creates a rich environment of meaning, within which interpretation can take place. The conclusion reached on Ecclesiastes 11:1-6 is that it adheres to the values of protest wisdom, but mnrkedly cynical and pessimistic. It advocates a "carpe diem" lifestyle, however, without escaping uncertainty. No interpretation is value-free and neither is this one. Hopefully it is sound within the created environment of meaning.